2012
DOI: 10.5603/fhc.2012.0033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sensitivity and specificity of real-time PCR and <i>in situ</i> hybridization in HPV16 and 18 detection in archival cervical cancer specimens

Abstract: Abstract:The aim of this study was to analyze the correlation between real-time PCR (RT-PCR) treated as a reference method and in situ hybridization with tyramide amplification system (ISH-TSA) in the detection of HPV16 and 18 infection and the assessment of viral genome status. The study was performed on cervical cancer biopsies fixed in 10% neutral buffered formalin and embedded in paraffin obtained from 85 women. TaqMan--based 5'exonuclease RT-PCR with type-specific primers was used to assess HPV16 and 18 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Viral DNA detection was positive by real-time PCR whereas viral RNA and DNA detection were negative on histological sections by ISH for Pacific oyster spat infected with the lowest dose (L). These results could be partly explained through the higher sensitivity of real-time PCR in comparison with ISH (Biesaga et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Viral DNA detection was positive by real-time PCR whereas viral RNA and DNA detection were negative on histological sections by ISH for Pacific oyster spat infected with the lowest dose (L). These results could be partly explained through the higher sensitivity of real-time PCR in comparison with ISH (Biesaga et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The HPV16 presence was determined on the basis of amplification of 81-bp fragment of virus E6 gene with primers (F: GAG AAC TGC AAT GTT TCA GGA CC, R: TGT ATA GTT GTT TGC AGC TCT GTG C) and TaqMan probe (6FAM-CAG GAG CGA CCC AGA AAG TTA CCA CAG TT-TAMRA), synthesized by Thermo Fisher Scientific, Waltham, USA, as previously described in detail (Biesaga et al 2012 ). In brief, amplification was carried out in a 25 µl mixture containing: 12.5 µl of Fast Universal PCR Master Mix (2 X), 100 nM of each primer, 300 nM of probe and 80 ng of DNA template.…”
Section: Methodsmentioning
confidence: 99%
“…Although previous studies have reported and identified endogenous retroviruses in bovine tissues (Baba et al., ; Nakaya & Miyazawa, ; Xiao, Kim, et al., ; Xiao, Park, et al., ), the current study is the first report on expression of endogenous retroviruses in pre‐implantation bovine embryo. We used RT‐qPCR technique with a very dynamic range and high sensitivity, specificity and accuracy (Benoy et al., ; Biesaga, Szostek, Klimek, Jakubowicz, & Wysocka, ; Cleusix, Lacroix, Dasen, Leo, & Le Blay, ; Tse et al., ). Our findings on the expression level of two BERVs, BERV‐K1 and BERV‐K2 envelope transcripts, reveal that these two ERVs are expressed throughout different stages of pre‐implantation development.…”
Section: Discussionmentioning
confidence: 99%